Understanding the Interplay Between Legal Morality, Corruption Penalization, and Public Patronage Culture: Evidence from a Systematic Literature Review - Appe Hutauruk; Fendi Maruba Parlindungan Hutahaean (Vifada Assumption Journal of Law, 2026)
Purpose: This study analyzes the ineffectiveness of normative-positivistic and repressive approaches to corruption eradication. It examines corruption's philosophical multidimensionalities, including justice concepts, and explains how power patronage, nepotism, and policy manipulation distort essential justice and undermine the welfare state. Research Design and Methodology: This study uses a normative research method combining a Systematic Literature Review (SLR) following PRISMA 2020 guidelines analyzing 87 articles with normative juridical analysis using statute, conceptual, and case approaches. Findings and Discussion: Corruption regularly destroys Aristotelian distributive and corrective justice and acts as the antithesis of John Rawls's just society by diverting resources to those with power. Corrupt public officials betray the legal system's internal morality, and Indonesia's entrenched patronage networks prioritize personal loyalty over formal bureaucracy, rendering current penalization ineffective at producing a deterrent effect. Implications: He study emphasizes the need for institutional reform to break patronage networks. It recommends treating corruption eradication not merely as a criminal law issue, but as an ethical project to build an anti-corruption state architecture pillared on accountability, transparency, and public integrity.